2010
DOI: 10.1007/s12610-010-0110-3
|View full text |Cite
|
Sign up to set email alerts
|

Priapisme aigu drépanocytaire: analyse de 20 cas traités au CHU de Brazzaville

Abstract: Objectif : Évaluer les résultats des traitements médicaux et chirurgicaux du priapisme drépanocytaire. Malades et méthodes : Vingt malades ont été traités pour priapisme drépanocytaire dans les services d'urologieandrologie et d'hématologie du CHU de Brazzaville, du 1 er janvier 1995 au 31 décembre 2005. Les méthodes thérapeutiques ont été les injections intracaverneuses d'étiléfrine et les fistules cavernospongieuses. Résultats : 1) Cinq patients traités sans succès par transfusion et étiléfrine orale ont été… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 7 publications
1
4
0
7
Order By: Relevance
“…We have a fairly large number of cases over a short study period in a relatively young population. These results are the same on those of Moby Mpah et al [5] in Cameroon, who report 33 cases of priapism, 19 of which were in sickle cell patients over a period of 36 months. In a prospective study conducted over 7 months in Congo, Okoko et al [6] reported a larger sample of 68 cases of priapism in sickle cell patients, but in 79.4% of cases it was intermittent priapism which did not require hospital care.…”
Section: Discussion and Commentssupporting
confidence: 91%
See 2 more Smart Citations
“…We have a fairly large number of cases over a short study period in a relatively young population. These results are the same on those of Moby Mpah et al [5] in Cameroon, who report 33 cases of priapism, 19 of which were in sickle cell patients over a period of 36 months. In a prospective study conducted over 7 months in Congo, Okoko et al [6] reported a larger sample of 68 cases of priapism in sickle cell patients, but in 79.4% of cases it was intermittent priapism which did not require hospital care.…”
Section: Discussion and Commentssupporting
confidence: 91%
“…In 16 cases (84.2%) a puncture of the corpus cavernosum and/or a distal cavernosal-spongiosum shunt according to Al Ghorab in 6 cases were associated with the treatment. Corpus cavernosum puncture is widely practised by Kassogue et al [4] in Mali, Moby Mpah et al [5] in Cameroon and Fall et al [10] in Senegal in 89%, 67.9% and 52.4% of cases respectively. However, several series [3] [8] [12] reveal that surgical management was necessary in the majority of cases.…”
Section: Discussion and Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to Kouamé et al [1], with 80% of patients maintaining a normal erection and good sexual function. Bouya et al [8] in Congo Brazzaville, Habou et al [15] in Niger, and Kassogué et al [11] in Mali found a lower result with respectively 50%, 58.3%, and 31% of patients having a normal erectile function. Falandry et al [12] report more alarming results with 56.8% of a total loss of erectile function.…”
Section: Discussionmentioning
confidence: 97%
“…The longer the delay, the higher the risk of permanent sexual dysfunction, since 66.7% of their patients treated within the first 72 hours recovered a normal erection, whereas only 25% of patients treated after this delay had a favorable evolution. Bouya et al [8] report that all ten patients with absent or insufficient erection were treated after the 30 th hour and that among the five patients treated with intracavernous injection of etilefrine, all three successes were observed in patients seen before the 24 th hour. Kamel et al [13] consider that the risk of secondary erectile dysfunction depends on several factors: the delay in treatment.…”
Section: Discussionmentioning
confidence: 99%